Translating marketing strategies into appearance of packaging design: a case of luxury merchandize - Khwanrat chinda; Nopadon Sahachaisaeree (My University, 2010)
This research attempts to test the purchasers' perception on product appearance on their credential and quality. Marketing strategy attempts to apply this approach in a number of ways, among them, packaging has been a means to reflect the type and position of products. A set of 3D packaging stimuli embedded with distinctive design elements and features assuming to determine purchasers' perceptions are utilized to test with a group of selected subjects on their cognitive and affective response reflected on the self-report questionnaire. Findings of the research are synthesized to form a design guideline for packaging which is able to boost the purchasers' buying decision.
Keywords: Credential; Guideline; Consumer Packaging Perceptions and Trends